PERANCANGAN INSINERATOR FIXED BED UPDRAFT TERINTEGRASI DENGAN SCRUBBER UNTUK MEMISAHKAN TAR - Eko Naryono; Arief Rachmansyah; Soemarno Soemarno (SENTIA 2016, 2016)
Incineration of household organic waste requires treatments of the flue gases to minimize pollutants. One type of pollutants in the flue gas incinerator product is tar, which is the result of the degradation of cellulose and lignin in biomass. One simple method of separation of tar from the exhaust gases is by absorption, using water as a medium scrubber. The scrubber water, before being discharged into the environment or reused needs to be treated to reduce pollutants. The purpose of this design was developed incinerator and scrubber system, which is integrated in one piece of equipment that can separate the pollutants in the flue gas, and tar from the water effectively. The working principle of the equipment is functioning to burn solid waste, absorbing the flue gas by scrubber and separate the tar from scrubber water by evaporation. Conceptually, based on visual observation of the product flue gas and waste water, the design of this incinerator can produce clean flue gas and waste water. Incinerators designed can reduce hydrocarbon content in the exhaust gases of up to 75% and tar in wastewater up to 76%.